Les Modes De Transformation De La Famille Kabyle - Ait Abdelkader, Mohamed Hichem; Chérifi, Kahina (جامعة الوادي - University of Eloued, 2021)
This article studies the Kabyle family, which is currently experiencing a new structural passage with urbanization and contemporary renovation. As well as the prevalence of individual and conjugal values over the norms and kinship values which have led to social and family restructuring and recomposition. Through a qualitative sociological approach, it turns out that the classic economic mode of operation of the village family community, based on joint ownership and autarky, is dissolving. Begun with the transformations included by colonization, and accompanied by the migratory phenomenon and rural exodus, these changes have continued under the action of urbanization, school education, and the mass media. Moreover, the theoretical foundations (in particular functionalist) estimated the nuclear or conjugal family as the system best in accordance with the parameters composing modern societies. Our study has shown that if the current trend in the city of Tizi-Ouzou is towards the nuclearization of socio-economic family units, it is important to underline the survival, despite the revolution in urban lifestyles, of a certain extended kinship organization. Le présent article étudie la famille kabyle qui vit actuellement un nouveau passage structurel avec l‟urbanisation et la rénovation contemporaine. De même que la prévalence des valeurs individuelles et conjugales sur les normes et valeurs parentèles qui ont amenées à la restructuration et la recomposition sociale et familiale. À travers une approche sociologique qualitative, il s‟avère que le mode de fonctionnement économique classique de la communauté familiale villageoise, fondé sur l‟indivision et l‟autarcie se dissout. Commencés par les transformations incluses par la colonisation, et accompagnés du phénomène migratoire et de l‟exode rural, ces changements se sont perdurés sous l‟action de l‟urbanisation, de l‟éducation scolaire, des mass médias. Par ailleurs, les fondements théoriques (notamment fonctionnalistes) estimaient la famille nucléaire ou conjugale comme le système le mieux en accord avec les paramètres composants les sociétés modernes. Notre étude a montré que si la tendance actuelle à la ville de Tizi-Ouzou est à la nucléarisation des unités socio-économiques familiales, il est important de souligner la survivance, en dépit de la révolution des modes de vie urbains, d‟une certaine organisation de parenté étendue.
مقال
Keywords: Nuclear family ; kabyle family; Extended family (tibal or village) ; Urbanization; Famille nucléaire ; famille kabyle ; Famille élargie (tibale ou villagoise); urbanisation